2005
DOI: 10.1073/pnas.0507124102
|View full text |Cite
|
Sign up to set email alerts
|

Polyproline II propensities from GGXGG peptides reveal an anticorrelation with β-sheet scales

Abstract: There is growing appreciation of the functional relevance of unfolded proteins in biology. However, unfolded states of proteins have proven inaccessible to the usual techniques for high-resolution structural and energetic characterization. Unfolded states are still generally conceived of as statistical coils, based on the pioneering work of Flory [(1969 T he process by which a protein acquires its native structure is among the most complex reactions known, and challenges remain in defining the nature of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
305
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(353 citation statements)
references
References 58 publications
41
305
7
Order By: Relevance
“…The experimental studies of Schweitzer-Stenner & Eker on trialanines 53,54 and tetraalanines 55 in water using polarized Raman, FT-IR and VCD spectroscopy confirm the dominance of PP II conformation in tetraalanines, while a 50:50 mixture of PP II and extended β-strand-like conformations was observed for trialanines. Other studies [56][57][58] , mostly from Kallenbach and colleagues, have confirmed that short alanine peptides form predominantly PP II conformation, which is in temperature dependent equilibrium with extended β-strand conformations. Taken together, these experimental findings suggest that short alanine peptides are found predominantly in PP II -like structures with varying degree of extended β-strand, and possibly smaller fractions of α-helical conformations.…”
Section: Force Field Validationmentioning
confidence: 85%
“…The experimental studies of Schweitzer-Stenner & Eker on trialanines 53,54 and tetraalanines 55 in water using polarized Raman, FT-IR and VCD spectroscopy confirm the dominance of PP II conformation in tetraalanines, while a 50:50 mixture of PP II and extended β-strand-like conformations was observed for trialanines. Other studies [56][57][58] , mostly from Kallenbach and colleagues, have confirmed that short alanine peptides form predominantly PP II conformation, which is in temperature dependent equilibrium with extended β-strand conformations. Taken together, these experimental findings suggest that short alanine peptides are found predominantly in PP II -like structures with varying degree of extended β-strand, and possibly smaller fractions of α-helical conformations.…”
Section: Force Field Validationmentioning
confidence: 85%
“…Recent experimental results suggest that the backbone preferences in proteins are already present in blocked aminoacids. 55,56 A number of experimental 55,[57][58][59][60] and theoretical, [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] studies indicate that the potential energy surface for AD in vacuum and in solution are considerably different: While in the gas-phase the global minimum is believed to be a C7 eq structure (ϕ− 83°, ψ~73°), 70 interaction with water favors the polyproline-II (P II , (ϕ~−75°, ψ~150°) conformation. 60 AD has also been used previously to investigate the performance of the SCC-DFTB method as compared to different classical force fields.…”
Section: Resultsmentioning
confidence: 99%
“…2). The negative band around 200 nm is characteristic of small unfolded peptides, while the band at 225 nm is due to the indole side chain of W (21,57), as seen in the CD spectrum of a peptide such as GGWGG containing a single chiral W residue (44). Each of the five peptides exhibits distinctive CD spectra in the presence of POPG and POPC.…”
Section: Resultsmentioning
confidence: 99%
“…CD spectroscopy is widely used to analyze the secondary structure of proteins and peptides because it is extremely sensitive to conformational changes. (RW) n in buffer appears to be unfolded due to the negative band around 200 nm that is characteristic of unfolded model peptides (44); the positive band around 225 nm due to the indole side chain is Trp specific (21,57). Peptide interactions with liposomes are accompanied by distinct CD spectral changes.…”
Section: Discussionmentioning
confidence: 99%